Outcome of fertility and pregnancy following hysteroscopic resection of septum using versapoint needle - Bhat, Vidya V.; Dutta, Indranil; Bhat, B. S.; Dutta, Dilip Kumar (Asian Journal of Medical Sciences, 2014)
Aim: The aim of the present study was to assess the safety and efficacy of hysteroscopic septum resection by Versapoint and future fertility outcome. 105 subfertile patients who underwent hysteroscopic septum resection using the Bipolar Versapoint system were analysed. Methods: Hysteroscopic Metroplasty was performed on 105 patients with uterine septum and history of infertility. The metroplasty procedure was performed on 105 patients using versapoint. The outcome was evaluated based on fertility outcomes. Study Design: Retrospective study Results: The pregnancy rates were noted to be around 96.5% following the procedure and live birth rate were around 82%. Conclusion: Hysteroscopic metroplasty using Bipolar Versapoint had better fertility outcomes and less risks. Future fertility and live birth rates had significantly improved. DOI: http://dx.doi.org/10.3126/ajms.v6i3.10904 Asian Journal of Medical Sciences Vol.6(3) 2015 63-65